Integrating Education for Sustainability into English as a Foreign Language Instruction in the Kingdom of Saudi Arabia - Alshahrani, Abeer (Curtin University, 2020)
This research analyses English as a Foreign Language (EFL) instruction in the context of sustainability using a case study mixed-methods approach, including document analysis, surveys and interviews, to determine to what extent Education for Sustainable Development (ESD) is understood and practised in the Kingdom of Saudi Arabia (KSA). Although KSA’s Vision 2030 sets ambitious goals for the country, there is much more needed to get ESD and gender parity represented in EFL curriculum.